Copper Mining in the Bronze Age at Mynydd Parys, Anglesey, Wales. (24th December 2021) - Jenkins, David A.; Timberlake, Simon; Davidson, Andrew; Mal, Kalla; Marshall, Peter; Mighall, Tim; O'Brien, Charlotte; Smith, David N.
Abstract : The Bronze Age in Britain is now a term often used to include both the first use of copper c . 2400 bc and also tin-bronze from c . 2100 bc, all of which required the extensive use of copper. Prehistoric mining for this metal has been identified in surface and underground workings in Parys Mine, Mynydd Parys, Anglesey, although almost all of the surface workings are now obscured by the extensive deep spoil from more recent mining in the industrial period. These copper-bearing ores are in bedded lodes, together with some intruded vein deposits. The Bronze Age workings have been exposed underground where they have been intersected by the early 19th century industrial workings on and above the 16 fathom and 20 fathom levels in the Parys Mine. Spoil exposures contain stone hammers ('mauls'), wood fragments, and charcoal; samples of the latter have been radiocarbon dated with chronological modelling suggesting activity took place in the first half of the 2nd millennium cal bc . Although relatively limited in extent, these important prehistoric mining sites are among the earliest found in the UK. They have survived due to their protection from surface erosion and limited accessibility.